AGGRESSIVE BEHAVIOR REVIEWED FROM ONLINE GAME ADDICTION IN ADOLESCENT BOYS IN CLASS VIII: CROSS SECTIONAL STUDY - Yudi Budianto; Gita Rahra Mirosa (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Online game addiction is a behavioral problem commonly experienced by adolescents and can lead to aggressive behavior. The increasing use of internet technology has made online games easily accessible, especially among students. This study aimed to determine the relationship between online game addiction and aggressive behavior among male eighth-grade students at SMP Negeri 13 Ogan Komering Ulu. This study used a quantitative method with a cross-sectional design. The population consisted of 117 students, with samples selected using purposive sampling. Data were collected using online game addiction and aggressive behavior questionnaires. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test. The results showed that 56 respondents (47.9%) experienced online game addiction, while 61 respondents (52.1%) did not. Aggressive behavior was categorized into low (32.5%), moderate (34.2%), and high (33.3%). The Chi-Square test showed a p-value of 0.001 (p < 0.05), indicating a significant relationship between online game addiction and aggressive behavior